Perception of tuberculosis among diabetics attending health training centres of a medical college hospital, Kancheepuram district, Tamil Nadu - Felicia J., Princy; D., Thirunaaukarasu; William, Roseline F.; Jennifer H., Gladius (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes mellitus, chronic non communicable disease triples the risk of developing tuberculosis by decreasing the immunity status. The prevalence of tuberculosis is higher in people with diabetes than in the general population, and diabetes is common co morbidity among people with tuberculosis. Health seeking behaviour of a patient depends up on their awareness of disease. The objective of this study was to determine the perception of tuberculosis among people with type 2 diabetes mellitus attending urban and rural health training centers. Methods: A facility based, comparative cross-sectional study was conducted among diabetics attending urban and rural training centres of a medical college hospital, Kancheepuram district. Sample size was estimated as 140. A semi structured questionnaire was used to interview the participants. Data was analysed using SPSS software 16v. Results: Among 140 participants, 70 were from rural setting and remaining of them from urban setting. The perception score was good among 31.4% of diabetics in urban and 8.6% among rural setting. The educational status, socio economic status and family history of tuberculosis were significantly associated with good perception score. Conclusions: The perception score was better in urban diabetes compared with rural diabetes patients. Health education measures will improve the health seeking behaviour.